Alteraciones genéticas vinculadas a la resistencia antibiótica en escherichia coli patogénica producida por el uso de antibióticos - Carrasco Velastegui, Pablo Francisco (2025)
Escherichia coli is a bacterium found in the digestive tract that is part of the human microbiota, responsible for various intra and extra intestinal infections, and controls the digestive cycle. E. coli antibiotic resistance is one of the main concerns in the scientific and health care world because it has exacerbated in the treatment of diseases in recent decades. The objective of this project is to determine the genetic alterations of E. coli linked to the use of antibiotics through a systematic literature review. For this, a PICO question was made, structured with various Boolean operators such as: OR, AND, and an information screening with PRISMA guidelines. 41 articles were selected for review, which describe various treatments for infections caused by this bacterium. The most common methods were third and fourth generation cephalosporins, fluoroquinolones and fosfomycins. Each pathotype of the bacteria has specific resistance and/or sensitivity against these antibiotics. Genes are responsible for the pathogenic resistance of E. coli. Among the most pathogenic resistant genes were blaCTX-M and mcr-1, which in addition to being resistant to broad-spectrum antibiotics, can combine to increase the severity of the infection and make its elimination difficult with multi-resistance to antibiotics.